2005
DOI: 10.1161/01.str.0000163084.16505.e3
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Angiotensin II in Excess Salt-Induced Brain Oxidative Stress of Stroke-Prone Spontaneously Hypertensive Rats

Abstract: Background and Purpose-The detailed role of angiotensin II in salt-exacerbated stroke is unclear. We examined the role of angiotensin II in salt-accelerated stroke of stroke-prone spontaneously hypertensive rats (SHRSP). Methods-Salt-loaded SHRSP were orally given the angiotensin II type 1 (AT1) receptor blocker candesartan (0.3 to 3 mg/kg per day) and calcium channel blocker amlodipine (1 mg/kg per day), and the effects on stroke (nϭ61) and brain superoxide were compared between them. We also examined the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 37 publications
6
52
0
Order By: Relevance
“…Moreover, salt loading had upregulated the inhibitory response of RSNA, AP, and HR to ICV DPI, an NADPH oxidase inhibitor, in the hypothalamus of DSs. In findings similar to the present data, brain oxidative stress production via NADPH oxidase had been reported in the salt-loaded stroke-prone SHR 18 and a central Ang II-induced hypertensive rat. 11,12 Primary cultures from the hypothalamus indicated that extracellular application of tempol and gp91ds-tat, a selective NADPH oxidase inhibitor, attenuated the Ang II-induced increase in the neuronal firing rate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, salt loading had upregulated the inhibitory response of RSNA, AP, and HR to ICV DPI, an NADPH oxidase inhibitor, in the hypothalamus of DSs. In findings similar to the present data, brain oxidative stress production via NADPH oxidase had been reported in the salt-loaded stroke-prone SHR 18 and a central Ang II-induced hypertensive rat. 11,12 Primary cultures from the hypothalamus indicated that extracellular application of tempol and gp91ds-tat, a selective NADPH oxidase inhibitor, attenuated the Ang II-induced increase in the neuronal firing rate.…”
Section: Discussionsupporting
confidence: 93%
“…16 Furthermore, salt loading increased superoxide production and NADPH oxidase activity in the brain of stroke-prone SHRs. 18 However, it has not yet been determined whether saltinduced ROS in the brain contributes to central sympathetic activation and AP elevation in salt-sensitive hypertension. The aim of the present study was, therefore, to elucidate whether the central sympathoexcitatory effect of oxidative stress mediates AP elevation in salt-sensitive hypertension.…”
mentioning
confidence: 99%
“…This botanical compound is derived from the root of Picrorhiza kurroa (Dodd-O and Pearse, 2000) and has been used as a Chinese medicinal herb for treatment of a number of infectious and inflammatory diseases (Hougee et al, 2006;Kim-Mitsuyama et al, 2005;Lafeber et al, 1999). Studies from our laboratory showed the ability for apocynin to protect against delayed neuronal death induced by global cerebral ischemia in the gerbil .…”
Section: Discussionmentioning
confidence: 98%
“…One of the more potent modulators of cardiovascular processes mediated by the NTS is Angiotensin II (AngII), a peptide that acts locally via the angiotensin AT-1A receptor to inhibit the baroreflex (12). These actions may be mediated by production of reactive oxygen species (ROS), molecules that are emerging as an important molecular substrate of central autonomic regulation, in addition to their better known role in mediating hypertension-induced cellular plasticity in the systemic vasculature (7,10,22,29,53).…”
Section: Introductionmentioning
confidence: 99%